Influence of the user's hand on mutual coupling of dual-antenna structures on mobile terminal - Azremi, Abdullah Al Hadi; Ilvonen, Janne; Li, Chung Huan; Holopainen, Jari; Vainikainen, Pertti V. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://www.ieee.org/